Tipos de HPV e câncer do colo uterino: impacto no prognóstico das pacientes com tumores nos estádios iniciais - Zampronha, Rossana de Araújo Catão (2008)
INTRODUCTION: The cervical cancer is the third most frequent malignant neoplasia among women in Brazil and it is responsible for the fourth cause of death for cancer. It is related among other causes to persistent infection by human papillomavirus. Doubts persist if HPV type could influence the tumor prognosis. OBJECTIVE: To study the prevalence of HPV 18 and HPV 16 in women presenting cervical cancer in clinic stage Ib, treated by radical hysterectomy with linfadenectomy, establishing prognostic correlation. METHODS: A retrospective cohort study, including 86 pacients with cervical cancer Ec I, submitted to radical hysterectomy, in a single center, in which were analysed the known prognostic factors and the positivity to HPV by PCR. Univariate analysis was performed, with Kaplan-Meir curves, for survival estimative. RESULTS: The prevalence of HPV 16 infection was 65.3% and HPV 18 prevalence was 33.3%. To both virus the prevalence was 26.9%. The overall survival for women presenting HPV 18 infection, in sixty months, was 91% and those women without HPV 18 infection, the overall survival was 96%. The overall survival for women with and without HPV16 infection was 94% and 96%, respectively. The disease free survival was not influenced by the presence of either virus. CONCLUSION: In the present study, in spite of the high prevalence of HPV 18 and HPV 16, the presence of these tipes of HPV have not influenced the prognosis of EcI cervixl cancer in women submitted to radical histerectomy.